2017
DOI: 10.1039/c7nj00125h
|View full text |Cite
|
Sign up to set email alerts
|

Structural isomerism of Ru(ii)-carbonyl complexes: synthesis, characterization and their antitrypanosomal activities

Abstract: New complexes with the formula [RuCl(CO)(dppb)(N–N)]PF6 were prepared by varying the CO position as well as the diimine ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Our research group evaluated the release of the CO molecule from ct‐ [RuCl(CO)(dppb)(bipy)]PF 6 by 13 C{ 1 H} NMR (DMSO‐d 6 ) and cyclic voltammetry. In that study, the compound exhibited a d 5 configuration after its oxidation from ruthenium(II) to (III) (after 48 hours), destabilizing the Ru‐CO bond and allowing dissociation of the CO molecule from the compound in the biological medium (Barbosa et al, ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our research group evaluated the release of the CO molecule from ct‐ [RuCl(CO)(dppb)(bipy)]PF 6 by 13 C{ 1 H} NMR (DMSO‐d 6 ) and cyclic voltammetry. In that study, the compound exhibited a d 5 configuration after its oxidation from ruthenium(II) to (III) (after 48 hours), destabilizing the Ru‐CO bond and allowing dissociation of the CO molecule from the compound in the biological medium (Barbosa et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…cyclic voltammetry. In that study, the compound exhibited a d 5 configuration after its oxidation from ruthenium(II) to (III) (after 48 hours), destabilizing the Ru-CO bond and allowing dissociation of the CO molecule from the compound in the biological medium (Barbosa et al, 2017).…”
Section: Comet Assaymentioning
confidence: 94%
“…It is worth pointing out that the arene ruthenium complexes which have been investigated as promising anticancer drugs [33–35] can be involved in the disruption of the cellular redox homeostasis via NADH transfer hydrogenation, as well as GSH metal thiol binding and oxidation [36] . Conversely, only few studies have been reported on the use of diphosphine ruthenium hydrogenation catalysts as efficient anticancer systems [37–40] …”
Section: Introductionmentioning
confidence: 99%
“…[36] Conversely, only few studies have been reported on the use of diphosphine ruthenium hydrogenation catalysts as efficient anticancer systems. [37][38][39][40] Herein we report the isolation of the cationic enantiomer complexes [RuX(CO)(PP)(phen)]Y (X, Y = carboxylates, thioacetate, PP = (R,R)-or (S,S)-Skewphos) [21] and their behaviour with (S)-cysteine and GSH via formation of aquo complexes. Remarkably different and very promising cytotoxic activity toward several cell lines has been observed for the couples of enantiomers.…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, they have never been tested in TH reactions with the NAD + /NADH couple. Recent studies also showed that this family of compounds are endowed with antiproliferative activity in cancer cells [33][34][35][36][37] . Therefore, we synthesized three Ru(II) monocarbonyl compounds (Scheme 1, complexes 1-3) featuring the same bidentate phosphine 1,4-bis(diphenylphosphino)butane (dppb) but different N^N ligands -namely ,2'-bipyridine (bipy), 1,10-phenanthroline (phen) and pyrazino [2,3-f] [1,10]phenanthroline (pzphen) -to explore the effects of the different aromatic scaffolds on the catalytic activity of the compounds.…”
Section: Introductionmentioning
confidence: 95%